Standards Framework for Intelligent Manufacturing Systems Supply Chain - Jardim-Goncalves, Ricardo; Agostinho, Carlos; Sarraipa, João; Togores, Amparo Roca de; Nuñez, Maria José; Panetto, Hervé (IntechOpen, 2011)
None